Site specific evaluation of pigeon pea (Cajanus cajan) variety IPA 203 through participatory approach - SINGH, A K; SINGH, R P; SINGH, V P; SINGH, R K; DIXIT, DEEPSHIKHA (The Indian Journal of Agricultural Sciences, 2021)
A site-specific evaluation of pigeon pea (Cajanus cajan (L.) Millsp.) variety IPA 203 was carried out through farmers participatory approach during two consecutive years, i.e. 2018-19 to 2019-20. The results revealed that the average yield 15.40 q/ha was recorded from pigeon pea variety IPA 203 as compared to farmers practice 9.79 q/ha and an average yield advantage registered up to 57.30% higher over the farmers’ practice. It was also observed that the higher number of primary branches/plant (6), number of pods/plant (385), seed index (14.80 g/100 seed), net returns (₹ 55147.5/ha) and BCR (3.52) from high yielding pigeon pea variety IPA 203 as compared to the farmers’ practice, i.e., 3, 313, 11.50, 9.79, ₹ 29490/- and 2.51, respectively. The growth and yield attributes were considerably lower under farmer’s practices because of considerable variation in the extent of adoption of recommended variety and technology depending upon the amount of risk involved in terms of cost, convenience, skill and knowledge about the concerned practice. Average extension gap, technology gap and technology index of pigeon pea were found 5.61, 4.60 q/ha and 23.00% respectively. Variations in the technology gap and index percentage were observed due to variation in agro-climatic parameters, soil fertility, biotic stresses, and socio-economic status and management practices. This variation can be narrowed down by encourage the farmers to adopt economical viable technologies of pulse crops. From evaluation of the technology, it can be concluded that replacement of local/old varieties with new varieties would increase the production and net income of the farmers.